Zebra finch males compensate in plumage ornaments at sexual maturation for a bad start in life. Issue 1 (December 2015) - Krause, E; Naguib, Marc
Abstract Background An individual's fitness in part depends on the characteristics of the mate so that sexually attractive ornaments, as signals of quality, are used in mate choice. Often such ornaments develop already early in life and thus are affected by nutritional conditions experienced then. Individuals thus should benefit by compensating as soon as possible for poor initial development of ornaments, to be attractive already at sexual maturity. Here, we tested whether early nutritional stress affects the cheek patch size of male Zebra finches (Taeniopygia guttata ), which are important in mate choice, and whether a small cheek patch size early on is compensated at sexual maturation. Furthermore we tested whether exploration behaviour is affected by such a compensation, as shown for other compensatory growth trajectories. Results Zebra finch males which were raised under poorer nutritional conditions initially expressed smaller cheek patches at day 50 post-hatching but then compensated in cheek patch size already at 65 days, i.e. when becoming sexually mature. Furthermore, compensatory growth in cheek patch during adolescence was negatively correlated with activity and exploration behaviour, measured in a novel environment. Conclusion This compensation in cheek patch size benefits male attractiveness but also was related to less exploration behaviour, an established proxy for avian personality traits. We discuss the possibility that compensatory priorities exist so that not all deficits from a bad start are caught-up at the same time. Resource allocation to compensate for poorly expressed traits is likely to have evolved to optimise traits by the time they are most beneficial.